2015
DOI: 10.1007/s11064-015-1743-6
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Differentiation Towards Neuronal Phenotype of SH-SY5Y Neuroblastoma Cells by Estradiol, Retinoic Acid and Cholesterol

Abstract: Human SH-SY5Y neuroblastoma cells maintain their potential for differentiation and regression in culture conditions. The induction of differentiation could serve as a strategy to inhibit cell proliferation and tumor growth. Previous studies have shown that differentiation of SH-SY5Y cells can be induced by all-trans-retinoic-acid (RA) and cholesterol (CHOL). However, signaling pathways that lead to terminal differentiation of SH-SY5Y cells are still largely unknown. The goal of this study was to examine in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
72
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 111 publications
9
72
0
3
Order By: Relevance
“…We have expanded the use of globular morphologies to different cell lines and showed that they attach and thrive. We also evaluate cell structure and verified morphological phenotypes indicative of normal, healthy, and developed cells as reported in the literature (Teppola et al, 2016). The use of less toxic surfactants in this study further encourages studies into globular LCE scaffolds that can support cell growth and be used without the concern of the surfactants' inherent toxicity.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…We have expanded the use of globular morphologies to different cell lines and showed that they attach and thrive. We also evaluate cell structure and verified morphological phenotypes indicative of normal, healthy, and developed cells as reported in the literature (Teppola et al, 2016). The use of less toxic surfactants in this study further encourages studies into globular LCE scaffolds that can support cell growth and be used without the concern of the surfactants' inherent toxicity.…”
Section: Resultssupporting
confidence: 68%
“…Cells can also be seen to stretch across several microspheres underlining their expansion within the matrix. The SEM images show morphological phenotypes indicative of matured cells [as indicated by Teppola et al (2016)]. Numerous neuritic extensions can be clearly seen in Figure 5Biii emanating from the cell body, resulting in the typical morphology of these cell types.…”
Section: Cell Studiesmentioning
confidence: 99%
“…The phenotypic outcome of this RA/BDNF differentiation protocol is, however, still somewhat controversial as it has been described as sympathetic cholinergic, based on evidence from target-directed qPCR and microarray studies which pointed into the direction of increased levels of acetylcholine transporter, choline acetyl transferase and neuropeptide Y [36, 37], but also as dopaminergic by others [38]. Moreover, inhibition of cell growth has not always been replicated when employing this procedure [24]. Additional protocols used for differentiation may involve combinations of the above-mentioned methods, or a combination of 10 μM RA and 0.3-5 mM dibutyryl cyclic adenosine monophosphate (dbcAMP) [39, 40], or of 10 μM RA for 3 days and 80nM tissue plasminogen activator [41] or the protocol was not specified.…”
Section: Main Textmentioning
confidence: 99%
“…RA results in a decrease in cell proliferation as well as maturation to the neuronal phenotype. [38] RA induced growth of neuritic extensions that continued throughout the experimental protocol (Figure 4, lower two images) resulting in a threefold increase in length compared to untreated cultures (Figure 4, table).…”
mentioning
confidence: 96%
“…To establish whether neurons can reliably mature in the developed constructs a subset of samples were treated with retinoic acid (RA) after four weeks to induce differentiation. RA results in a decrease in cell proliferation as well as maturation to the neuronal phenotype 38. RA induced growth of neuritic extensions that continued throughout the experimental protocol (Figure 4, lower two images) resulting in a threefold increase in length compared to untreated cultures (Figure 4, table).…”
mentioning
confidence: 96%